2013
DOI: 10.1038/am.2013.56
|View full text |Cite
|
Sign up to set email alerts
|

β-MnO2 nanorods with exposed tunnel structures as high-performance cathode materials for sodium-ion batteries

Abstract: Sodium-ion batteries are being considered as a promising system for stationary energy storage and conversion, owing to the natural abundance of sodium. It is important to develop new cathode and anode materials with high capacities for sodium-ion batteries. Herein, we report the synthesis of b-MnO 2 nanorods with exposed tunnel structures by a hydrothermal method. The as-prepared b-MnO 2 nanorods have exposed {111} crystal planes with a high density of (1 Â 1) tunnels, which leads to facile sodium ion (Na-ion)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 26 publications
2
56
0
Order By: Relevance
“…Surprisingly, when the β-MnO 2 exposed (111) facets, which had exposed (1 × 1) ionic diameter tunnels that provide facile transport for Na-ion insertion, accommodation [48]. Copyright 2013, Wiley and extraction, it delivered a high initial specific capacity of 350 mAh g −1 and achieved good high-rate performance [50]. This confirms the importance of the electrochemical intercalation anisotropy for different crystalline facets of electrode materials.…”
Section: Layered Transition Metal Oxidesmentioning
confidence: 73%
See 1 more Smart Citation
“…Surprisingly, when the β-MnO 2 exposed (111) facets, which had exposed (1 × 1) ionic diameter tunnels that provide facile transport for Na-ion insertion, accommodation [48]. Copyright 2013, Wiley and extraction, it delivered a high initial specific capacity of 350 mAh g −1 and achieved good high-rate performance [50]. This confirms the importance of the electrochemical intercalation anisotropy for different crystalline facets of electrode materials.…”
Section: Layered Transition Metal Oxidesmentioning
confidence: 73%
“…The dominantly exposed (100) crystal planes provided facile ionic transport for Na + -ion insertion and extraction. They further investigated different β-MnO 2 nanorod electrode materials for the Na-ion batteries and clearly demonstrated that, with different exposed crystal planes, there are hugely different electrochemical performances [49,50]. As shown in Fig.…”
Section: Layered Transition Metal Oxidesmentioning
confidence: 99%
“…[2][3][4][5][6] Rechargeable sodium-ion batteries have chemical storage mechanisms similar to their lithium-ion counterparts and are expected to be low cost and chemically sustainable as a result of an almost infinite supply of sodium. [7][8][9][10][11][12][13][14][15] Meanwhile, the feasible replacement of Cu with Al current collectors (an alloying reaction does not occur between Na and Al) will further reduce the substantial costs and weight for nextgeneration batteries.Layered sodium oxide Na x MeO 2 (Me = 3d transition metal) materials, owing to their large specific capacity and reversible insertion/ …”
mentioning
confidence: 99%
“…Among various pseudocapacitive materials, manganese oxides (MnO x ) have attracted the strongest interest because of their natural abundance, low cost and environmental friendliness. 10 Numerous studies have reported the hybrid structures of carbon materials with electrochemically active manganese oxide (MnO x ), most commonly MnO 2 . 7 However, the maximum specific capacitance of MnO 2 in these reports remains low, at approximately 300-400 F g − 1 , and the capacitance of overall hybrids is even lower, typically o200 F g − 1 ; 11 MnO 2 still displays low electrical conductivity, limited stability and poor integration in hybrid electrode systems.…”
Section: Introductionmentioning
confidence: 99%